2012
DOI: 10.1111/j.1467-2979.2012.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

The implications for aquaculture practice of epigenomic programming of components of the endocrine system of teleostean embryos: lessons learned from mammalian studies

Abstract: Epigenetics is the study of changes in gene expression patterns that occur without any modification of the underlying nucleotide sequence of the DNA. Modifications of the so‐called epigenome include complex transient or permanent chemical changes of the DNA or histone proteins resulting in the suppression or enhancement of gene expression, together with an array of post‐translational events that modify the translational products. Epigenomic programming (EP) of the genome is an essential component of embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 194 publications
(228 reference statements)
0
26
0
Order By: Relevance
“…). It has been suggested that environmental stimuli may induce epigenetic changes, which in turn can affect gene expression patterns in novel environments (Li and Leatherland ). It is thus possible that alternative molecular mechanisms, such as gene expression tuning (Roberge et al.…”
Section: Discussionmentioning
confidence: 99%
“…). It has been suggested that environmental stimuli may induce epigenetic changes, which in turn can affect gene expression patterns in novel environments (Li and Leatherland ). It is thus possible that alternative molecular mechanisms, such as gene expression tuning (Roberge et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other components of the egg such as thyroid or sex steroid hormones (de Jesus & Hirano, 1992) or microRNA (Ma et al, 2015) may be causing the observed differences in offspring. Epigenetic programming is an established mechanism of intergenerational change in mammals (reviewed in Dunn et al, 2011), and emerging as a candidate mechanism in oviparous taxa as well (Lindqvist et al, 2007;Li & Leatherland, 2013). Continued exploration and methodological refinement of assessing changes to gamete and offspring epigenome in fish is warranted.…”
Section: Discussionmentioning
confidence: 98%
“…; Jonsson & Jonsson ). In a recent review, Li & Leatherland () concluded that hatchery rearing might be expected to have an influence on epigenetic programming, particularly of genes related to endocrine processes. Such processes are known to be critical to juvenile imprinting in salmon, and altered hormone profiles have been suggested to lead to increased straying of hatchery‐origin fish (reviewed by Keefer & Caudill ).…”
Section: Discussionmentioning
confidence: 99%